The association between presentence risk evaluations and sentencing outcome - Jung, Sandy; Ennis, Liam; Brown, Kelsey; Ledi, Denise (My University, 2015)
Presentence risk evaluations are routinely submitted to judges prior to sentencing with the goal of guiding treatment recommendations and informing sentencing decisions. Empirical research has yet to examine this association. In the present study, the correspondence between presentence risk evaluations and sentencing outcomes was explored using the files of 165 offenders who had completed LSI-R, LS/CMI, and/or HCR-20 protocols. We found that sentencing outcome was associated with risk assessment scores, particularly from the Level of Service Measures. This study's findings suggest that presentence risk evaluations have a strong association with the sentencing decisions of the judiciary, suggesting that sentencing procedures may reflect evidence-based practice.
Keywords: risk assessment; sentencing; incarceration; level of service measures; HCR-20